Disclosure of individual research results in clinico-genomic trials: challenges, classification and criteria for decision-making. Issue 5 (23rd February 2011) - Kollek, Regine; Petersen, Imme
Abstract : While an ethical obligation to report findings of clinical research to trial participants is increasingly recognised, the academic debate is often vague about what kinds of data should be fed back and how such a process should be organised. In this article, we present a classification of different actors, processes and data involved in the feedback of research results pertaining to an individual. In a second step, we reflect on circumstances requiring further ethical consideration. In regard to a concrete research setting—the one of clinico-genomic research—we discuss what kinds of difficulties have to be faced when returning individual research results to trial participants. In a last step, we elaborate on a stepwise model to trigger the individual feedback process. Hence, this paper gives guidance on how to feedback individual research results in a specific research setting and responds at the same time to new challenges in the debate on the duty to return individual research findings.